Physiological and Biogeochemical Responses of Super-Corals to Thermal Stress from the Northern Gulf of Aqaba, Red Sea - Grottoli, Andréa G.; Tchernov, Dan; Winters, Gidon (Frontiers in Marine Science, 2017)
Mass coral bleaching is increasing in frequency and severity, leading to the loss of coral abundance and diversity. However, some corals are less susceptible to bleaching than others and can provide a model for identifying the physiological and biogeochemical traits that underlie coral resilience to thermal stress. Corals from Eilat in the Gulf of Aqaba in the northern Red Sea do not bleach unless seawater temperatures are sustained at +6⁰C or higher above their average summer maximum. This extreme thermal tolerance qualifies these as super-corals, as most corals bleach when exposed to temperatures that are only +1-2⁰C above their thermal maximum. Here, we conducted a controlled bleaching experiment (+6°C) for 37 days (equivalent to 32-degree heating weeks) on three species of corals from Eilat: Stylophora pistillata, Pocillopora damicornis, and Favia favus. To assess the response of the holobiont to thermal stress, the following variables were measured on each coral: endosymbiotic algal cell density, Chlorophyll a, endosymbiotic mitotic cell division, total lipids, protein, carbohydrate, and the stable carbon (d13C) and oxygen (d18O) isotopic composition of the skeleton and the d13C of the animal host tissue and endosymbiotic algae. While all three species appeared visibly bleached, their physiological and biogeochemical responses were species-specific. S. pistillata catabolized lipids but still maintained total energy reserves and biomass. Increases in both skeletal d13C and d18O indicates that calcification declined in this species. P. damicornis was the least affected by bleaching. It maintained its total energy reserves and biomass, and isotopic evidence suggests that it maintained calcification and was not dependent on heterotrophy for meeting metabolic demand when bleached. Finally, F. favus catabolized protein and carbohydrates, and suffered losses in total energy reserves and biomass. Nevertheless, isotopic evidence suggest that photosynthesis and calcification were maintained, and that this species has a high baseline heterotrophic capacity. Thus, just like their non-super-coral counterparts, maintaining energy reserves and biomass, and heterotrophic capacity appear to be traits that underlie the thermal tolerance of these super-corals from Eilat. Given the high thermal tolerance of these super-corals, these populations could provide viable seed stock for repopulating coral losses on other reefs.